A lumped kinetic model for high-temperature pyrolysis and combustion of 50 surrogate fuel components and their mixtures. (15th February 2021) - Zhang, Xiaoyuan; Mani Sarathy, S.
Highlights: An updated decoupling methodology is proposed to develop multi-component fuel models. Develop a lumped mechanism for 50 fuel components from various chemical classes. Validate the model against the targets from 30 pure fuels and 12 fuel mixtures. Abstract: Wide distillation fuels (WDF) and gasoline/diesel blends have been proposed as new fuel formulations for advanced combustion engines. Recent studies have shown that multi-component gasoline and diesel surrogate mixtures can accurately mimic the distillation curve, functional group or hydrocarbon class distribution, average molecular weight, and other combustion properties of real fuels. This work presents an updated decoupling methodology to construct a 50-component fuel model, which consists of a skeletal sub-mechanism for large hydrocarbon components present in gasoline, jet and diesel fuels, a reduced C5 -Cn mechanism, and a detailed C0 -C4 mechanism. The entire model contains 156 species and 1132 reactions. The chemical classes covered include n -alkanes, iso -alkanes, cyclo -alkanes and alkylbenzenes. Compared with the comprehensive detailed kinetic modeling approach, the present methodology largely reduces the model size due to the use of skeletal fuel mechanisms. Compared with the traditional decoupling methodology, our approach increases the model accuracy since it contains a detailed C0 -C4 mechanism instead of a reduced C2 -C3 mechanism. The present model was validated against experimental targets at high temperatures, including the pyrolysis and oxidation speciation data and global parameters such as ignition delay times and laminar flame speeds from 30 pure fuel components and 12 fuel mixtures. In general, the present model performs well against these experimental data, suggesting this methodology is a suitable approach for developing accurate kinetic models for multi-component fuels. Future work will extend the present framework to predict low-temperature combustion chemistry of multi-component fuels.